Prospective Comparative Study on Endothelial Corneal Cell After Cataract Surgery Using Torsional vs Longitudinal Phacoemulsification - Precisza Fanny Faranita; Wisnu Sadasih; A. Rizal Fanany; Maharani Maharani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Objectives: Our aim was to compare endothelial corneal cell changes after cataract surgery performed with Torsional and Longitudinal phacoemulsification in patient with senile cataract. Methods: In this prospective study, the patients were divided into two groups, 24 eyes underwent cataract surgery using Torsional (OZil Infiniti Vision System, Alcon) and 23 eyes using Longitudinal phacoemulsification (Stelaris, Bausch & Lomb). Preoperative, 1 day, and 1-week post-operative examinations on endothelial corneal cells were performed using specular microscope. Cataracts were subdivided according to the LOCS III grading of nucleus. Intraoperative parameters using phacoemulsification time were evaluated. Results: On the results of CCT at 1 day and 1-week post-operative, there were significant changes in group Torsional and Longitudinal 601±68.67; 562.22±45.48 (p=0.033) and 561,71±36,37; 519.52±79.93 (p = 0.015). However, there were no significant changes of CD, CV, HEX 1 day and 1 week post operatively between two groups. The phacoemulsification time was lower in group Torsional 17.11±15.86 seconds than group Longitudinal 18.53±15.46 seconds (p=0.595) but not significantly different. Conclusions: Torsional phacoemulsification outperforms the Longitudinal with a lower phacoemulsification time on soft and medium cataracts, but the differences were not significant. Torsional caused more corneal edema at 1 day and 1 week postoperative significantly and more endothelial cell losses but insignificantly.